FINANCIAL DEVELOPMENT AND REMITTANCES IN RBMU'S COUNTRIES - R. Bratu (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка, 2016)
The aim of this paper is to evaluate the state of development of financial system from 3 of those countries that European Union has established relation through Partnership Program, added Romania also. The research is based on the empirical evidence about the structure and performance of financial systems from RBMU's countries (Romania, Belarus, Ukraine and Moldova). The results are correlated with the influence of remittances inflows in fostering the development of financial systems, especially banking systems, analyzed from the reverse casualty approach.